2021
DOI: 10.3389/fpls.2021.744175
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Quantitative Trait Nucleotides and Candidate Genes for Bacterial Wilt Resistance in Tobacco (Nicotiana tabacum L.) Using Genotyping-by-Sequencing and Multi-Locus Genome-Wide Association Studies

Abstract: Tobacco bacterial wilt (TBW) is a devastating soil-borne disease threatening the yield and quality of tobacco. However, its genetic foundations are not fully understood. In this study, we identified 126,602 high-quality single-nucleotide polymorphisms (SNPs) in 94 tobacco accessions using genotyping-by-sequencing (GBS) and a 94.56 KB linkage disequilibrium (LD) decay rate for candidate gene selection. The population structure analysis revealed two subpopulations with 37 and 57 tobacco accessions. Four multi-lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 78 publications
(134 reference statements)
2
3
0
Order By: Relevance
“…We compared the expression data of leaves at 1, 6, and 12 h with the control, identifying 10,153, 7,879, 7,662, 13,704, 5,161, and 7,438 DEGs in HS-1h, HS-6h, HS-12h, HT-1h, HT-6h, and HT-12h, respectively (Figures 2A-C). Further, these genes were involved in cell division, cellular process, response to stimulus, primary metabolic process, response to heat, the developmental process involved in reproduction, photosynthesis, detoxification, RNA binding, and auxin homeostasis (Figures 3, S2, S3) in line with previous studies (Wang et al, 2016;Cai et al, 2020;Helal et al, 2021;Lai et al, 2021). In addition, most DEGs were enriched in the MAPK signaling pathwayplant, brassinosteroid biosynthesis, plant-pathogen interaction, plant hormone signal transduction, and circadian rhythm (Figures 3, S4, S5); these results are similar to previous reports (Song et al, 2014a;Song et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We compared the expression data of leaves at 1, 6, and 12 h with the control, identifying 10,153, 7,879, 7,662, 13,704, 5,161, and 7,438 DEGs in HS-1h, HS-6h, HS-12h, HT-1h, HT-6h, and HT-12h, respectively (Figures 2A-C). Further, these genes were involved in cell division, cellular process, response to stimulus, primary metabolic process, response to heat, the developmental process involved in reproduction, photosynthesis, detoxification, RNA binding, and auxin homeostasis (Figures 3, S2, S3) in line with previous studies (Wang et al, 2016;Cai et al, 2020;Helal et al, 2021;Lai et al, 2021). In addition, most DEGs were enriched in the MAPK signaling pathwayplant, brassinosteroid biosynthesis, plant-pathogen interaction, plant hormone signal transduction, and circadian rhythm (Figures 3, S4, S5); these results are similar to previous reports (Song et al, 2014a;Song et al, 2021).…”
Section: Discussionsupporting
confidence: 90%
“…Our previous research identified expressed sequence tagsimple sequence repeat (EST-SSR) markers in flowering Chinese cabbage (Chen et al, 2017) and also detected significant SNPs/ genes for plant height (Ikram et al, 2022a;Ikram et al, 2022b;Li et al, 2022) and wilt resistance (Lai et al, 2021) in tobacco. The present study used RNA-seq based on the Illumina HiSeq2000 platform to undertake a genome-wide analysis of gene expression in leaves of HT (Youlu-501) and HS (3T-6) flowering Chinese cabbage varieties under heat stress (0, 1, 6, and 12 h) to (1) identify DEGs in HS and HT genotypes after 1, 6, and 12 h of heat stress: (2) annotate these genes based on gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis; (3) identify the expression pattern of genes using Hierarchical clustering analysis; (4) identify TFs associated with the DEGs and their role in heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…3-5), indicating some accessions from the same source could not cluster together and confirmed no clear pattern for geographical source, consistent with other reports (Fricano et al 2012;Xia et al 2013;Liu et al 2017). Interestingly, in PCoA, both groups had mixed accessions, indicating that most tobacco varieties examined are of mixed origin (Kalivas et al 2016;Lai et al 2021). Similarly, the pedigree information of 50 tobacco accessions (Table 1) showed that Chinese tobacco accessions originated from USA accessions and have a common ancestry.…”
Section: Discussionsupporting
confidence: 82%
“…Glyoxylate and dicarboxylate metabolism bypass the TCA cycle, participate in energy metabolism, and are important in fungal infections 30 . Glutathione metabolism is involved in biological processes such as ferroptosis and antioxidation 31 , and glutathione is a major antioxidant that maintains redox homeostasis, which is closely associated with inflammatory responses 32 . Steroid hormone biosynthesis and primary bile acid biosynthesis involved in pathogenesis of acute and chronic infections in mice 33 .…”
Section: Discussionmentioning
confidence: 99%